Entre a pré-história e a história: em busca de uma cultura histórica sobre os primeiros habitantes do Cariri Paraibano - Oliveira, Adriana Machado Pimentel de (2009)
The historical Culture is a thematic one argued currently in the Brazilian historiografy, and the objective of this work is to treat it by means of a boarding that understands the quarrels on material culture, memory and identity and, in such a way, to present the referring historical culture to the first inhabitants of the Cariri paraibano through the analysis of the data proceeding from archaeology and the historiografy. For in such a way, one uses an established theoretical recital in the quarrels on Historical Culture, Region, Material Culture and Archaeology and presents it relation between the archaeological data and the historical references on the aboriginal occupation in this region, as a form of becoming possible the construction of the same one. As methods resource used to demonstrate this construction if it opted to showing uncurling of the studies related to the Culture and its importance for History and Archaeology. At the second, to understand the occupation of the called space of Cariri paraibano in the period Colonial had been made quarrels on the constitution of this space and the paper of the responsible agents for the occupation of the same. The debates on Regional History and the environment of the half-barren one are determinative for the conception of the area today called of Cariri paraibano. In the referring quarrels to Archaeology, it was looked to discourse on the archaeological research that had occurred north-eastern Brazilian and the carried through research, specifically, in this considered area. To analyze the raised sources and to be able to conclude if exist, or not, a referring historical culture to the occupation of the first inhabitants of the Cariri paraibano if it became our objective for the conclusion of this work.